Enterovirus 71 uses cell surface heparan sulfate glycosaminoglycan as an attachment receptor - Tan, Chee Wah; Poh, Chit Laa *; Sam, I-Ching; Chan, Yoke Fun (American Society for Microbiology, 2013)
Enterovirus 71 (EV-71) infections are usually associated with mild hand, foot, and mouth disease in young children but have been reported to cause severe neurological complications with high mortality rates. To date, four EV-71 receptors have been identified, but inhibition of these receptors by antagonists did not completely abolish EV-71 infection, implying that there is an as yet undiscovered receptor(s). Since EV-71 has a wide range of tissue tropisms, we hypothesize that EV-71 infections may be facilitated by using receptors that are widely expressed in all cell types, such as heparan sulfate. In this study, heparin, polysulfated dextran sulfate, and suramin were found to significantly prevent EV-71 infection. Heparin inhibited infection by all the EV-71 strains tested, including those with a single-passage history. Neutralization of the cell surface anionic charge by polycationic poly-D-lysine and blockage of heparan sulfate by an anti-heparan sulfate peptide also inhibited EV-71 infection. Interference with heparan sulfate biosynthesis either by sodium chlorate treatment or through transient knockdown of N-deacetylase/N-sulfotransferase-1 and exostosin-1 expression reduced EV-71 infection in RD cells. Enzymatic removal of cell surface heparan sulfate by heparinase I/II/III inhibited EV-71 infection. Furthermore, the level of EV-71 attachment to CHO cell lines that are variably deficient in cell surface glycosaminoglycans was significantly lower than that to wild-type CHO cells. Direct binding of EV-71 particles to heparin-Sepharose columns under physiological salt conditions was demonstrated. We conclude that EV-71 infection requires initial binding to heparan sulfate as an attachment receptor.